PSYCHOLOGISM AS A LEADING IMAGE METHOD IN A HISTORICAL WORK (Scientific journal of the Fergana State University, 2025)
The article discussed such issues as the poetics of the historical novel, the unity of form and content of the work of art, the plot and composition of the work, the harmony of the theme and idea, the proportionality of the historical truth and artistic texture, the language of the work of art, and psychologism as a leading image in the historical novel.